Upaya Meningkatkan Minat Membaca Masyarakat Desa Cibeuteung Udik Melalui Program ‘Saung Baca’ - Apriyanti, Dwi; Nabilah, Nurul; Sarinah, Ika; Mufidah, Vika Nurul (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
The purpose of this service is to increase interest in reading for early childhood children in Cibeteung Udik Village, Kp. Mosque Block. As a result of this activity, KKN students were able to complete the program, namely by establishing a 'Saung Baca' and increasing children's interest in reading.